Penerapan Casework Dalam Membangun Kesadaran Bahaya Perundungan pada Siswa UPT SMPN 10 Medan - Gresia Amelia; Fajar Utama Ritonga; Gusti Pirandy (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Attitude is the basis of a person's judgment and behavior, the character of the nation that must be upheld, one of which is mutual respect, not only for elders but fellow human beings regardless of genes, age and position. Mutual respect must be built from an early age, before building a generation of accomplished nations, mutual respect must be applied first. the development of the times and technology is none other than the biggest influence in influencing and hindering the building of the national character as expected, this is very much felt when starting kampus mengajar program’s. therefore the purpose of writing this journal is to build an attitude of mutual respect as well as the dangers of bullying among UPT SMPN 10 Medan, Padang Bulan students, with a period of 3 months. With the help of the staged casework method by Zastrow. The stages in the groupwork method include (1) Engagement, Intake, Contract, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. This method shows a positive development in the attitude of students at UPT SMPN 10 Medan.